Dissolution périodique du nickel dans l'acide nitrique en présence de chlorures - Vincent J. Farage; J.-J. Schaer; D. Janjic (CHIMIA)
In the presence of Cl-, nickel dissolves periodically in HNO3 for normalities between 9 < N < 17. This phenomenon is investigated by potentiometry and thermometry.